2015
DOI: 10.1210/jc.2014-3450
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Pancreatic Polypeptide Concentrations Predict Visceral and Liver Fat Content

Abstract: Context and objective:No current biomarker can reliably predict visceral and liver fat content, both of which are risk factors for cardiovascular disease. Vagal tone has been suggested to influence regional fat deposition. Pancreatic polypeptide (PP) is secreted from the endocrine pancreas under vagal control. We investigated the utility of PP in predicting visceral and liver fat.Patients and Methods:Fasting plasma PP concentrations were measured in 104 overweight and obese subjects (46 men and 58 women). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
17
1
1
Order By: Relevance
“…Pancreatic polypeptide, a 36-amino-acid peptide, is released from the pancreatic polypeptide cells (31). It inhibits pancreatic exocrine secretion, food intake, gastric emptying, and gallbladder contraction (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic polypeptide, a 36-amino-acid peptide, is released from the pancreatic polypeptide cells (31). It inhibits pancreatic exocrine secretion, food intake, gastric emptying, and gallbladder contraction (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic polypeptide, a 36-amino-acid peptide, is released from the pancreatic polypeptide cells (31). It inhibits pancreatic exocrine secretion, food intake, gastric emptying, and gallbladder contraction (31). Although the majority of previous studies have investigated meal-induced pancreatic polypeptide secretion, several studies in the settings of both pancreatic diseases and type 2 DM have studied fasting pancreatic polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Arosio et al [ 45 ] showed that intravenous administration of ghrelin in healthy subjects resulted in increased fasting levels of PP. Pancreatic polypeptide is also associated with adiposity and has been demonstrated to be a biomarker of abdominal adiposity [ 46 ] as well as a biomarker for visceral and intra-hepatocellular fat content in overweight individuals [ 47 ]. Pancreatic polypeptide levels are known to differ between ethnicities, where in Pima Indians PP is elevated (both in fasting state and postprandially) compared to Caucasians [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma glucagon was measured by radioimmunoassay (Millipore, St. Charles, Miss, USA). Serum PP was measured using an established radioimmunoassay in the Section of Investigative Medicine, Imperial College London [25] . Briefly, 100 μl of sample were added to 600 μl of 0.05 M phosphate buffer with 0.3% bovine serum albumin (BSA) w/v containing antibody (titer 1:860,000).…”
Section: Methodsmentioning
confidence: 99%